Botanic Gardens - (:unkn) unknown (My University, 2009)
Colour: Black and White; Style: Portrait; Other: Bordered, Undivided
A picture of a path lined with tall trees leading through the Botanical Gardens. Along the path is a man standing against a tree. Affixed to the postcard is a Trinidad and Tobago 1 penny stamp.
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Trees--Trinidad and Tobago; 1905; Men--Trinidad and Tobago; Men's clothing--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago